Verrucous Carcinoma of Vulva: An Unusual Case Report - Jaya Patel; Deepa Masand (International Journal of Medical Research and Review, 2014)
Introduction: Verrucous carcinoma of the vulva is a variant of squamous cell carcinoma and is a rare type of vulvar cancer, consisting 1-2 % of vulvar cancer overall .It is locally invasive and rarely metastasize. The aetiology is not known.Case report: A 60 year old postmenopausal, multipara Indian woman presented in July 2012 with anexophytic irregular growth that was locally destructive associated with vulvar itching, pain and change in skin colour in the OPD of Obstetrics and Gynaecology department of NIMS Medical College, Jaipur (Rajasthan), India. She was a chronic smoker. Local examination shows 5-6 cm raised verrucous growth on the lower part of right labia majora with 1 cm ulcer at tip. Complete evaluation revealed verrucous carcinoma of vulva FIGO stage IB with no lymph node involvement. The patient was treated with an extensive excision of the damage and radiotherapy was advised.